2020
DOI: 10.1021/jacs.0c04764
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary Hierarchical Complexity in Assemblies of Sulfur-Bridged Metal Chiral Clusters

Abstract: Self-assembly of three-dimensional structures with order across multiple length scaleshierarchical assemblyis of great importance for biomolecules for the functions of life. Creation of similar complex architectures from inorganic building blocks has been pursued toward artificial biomaterials and advanced functional materials. Current research, however, primarily employs only large, nonreactive building blocks such as Au colloids. By contrast, sulfur-bridged transition metal clusters (<2 nm) are able to off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…Chirality is a ubiquitous type of geometric symmetry in which an object and its mirror-image counterpart cannot be superimposed. Ligand-protected atomically precise superatomic metal clusters are among the most promising nanoscale materials that are modeled to investigate their precise structure–property relationships. Since the chiral Au 38 cluster was first characterized in 2010, the synthesis and separation of enantiomers of metal clusters have gained increasing interest. Single-crystal X-ray crystallography enables us to see the absolute chiral conformation of metal clusters, and electronic circular dichroism (ECD) signals verify the ground-state chiroptical activity of nanoclusters. However, CPL that stems from chiral excited states of luminescent materials is very scarce among well-defined superatomic metal clusters because integrating the three basic requirements, namely, perfect single crystals, high-efficiency luminescence, and pure enantiomers, into one superatomic metal cluster remains a considerable challenge. , In particular, the near-infrared (NIR) emission energies of superatomic nanoclusters commonly show a very low quantum efficiency (QY < 0.001). …”
mentioning
confidence: 99%
“…Chirality is a ubiquitous type of geometric symmetry in which an object and its mirror-image counterpart cannot be superimposed. Ligand-protected atomically precise superatomic metal clusters are among the most promising nanoscale materials that are modeled to investigate their precise structure–property relationships. Since the chiral Au 38 cluster was first characterized in 2010, the synthesis and separation of enantiomers of metal clusters have gained increasing interest. Single-crystal X-ray crystallography enables us to see the absolute chiral conformation of metal clusters, and electronic circular dichroism (ECD) signals verify the ground-state chiroptical activity of nanoclusters. However, CPL that stems from chiral excited states of luminescent materials is very scarce among well-defined superatomic metal clusters because integrating the three basic requirements, namely, perfect single crystals, high-efficiency luminescence, and pure enantiomers, into one superatomic metal cluster remains a considerable challenge. , In particular, the near-infrared (NIR) emission energies of superatomic nanoclusters commonly show a very low quantum efficiency (QY < 0.001). …”
mentioning
confidence: 99%
“…The linear correlation of the peak current of the anode (I pa ) vs the square root of the scan rate (ν 1/2 ) (Figure 4b inset) indicated that the electrochemical process is diffusion-controlled. 66,67 This has a similar electrochemical evolution trend to P 5 W 30 (Figure S10). Remarkably, the SD/Ag43a carbon paste electrode is stable.…”
Section: ■ Experimental Methodsmentioning
confidence: 59%
“…[8] Furthermore,t he work reported by Jin and Robinson for the observation of hierarchical complexity in thiolatestabilized metal NCs and their assemblages nicely demonstrated their similarity to natural living systems. [9] It should be noted, however, that although chiral arrangement was observed in hierarchical nanostructures reported by Jin and Robinson, they were racemic in nature.H ere,w e report the synthesis and structure of tertiary chiral nanostructures with 100 %o ptical purity.I nt his work, novel trimetallic chiral clusters,n amely,[ Au 7 Ag 6 Cu 2 (R-o rS-BINAP) 3 (SCH 2 Ph) 6 ] + ,a st he SbF 6…”
Section: Introductionmentioning
confidence: 93%